Aula invertida en el aprendizaje de integrales definidas en los estudiantes de quinto semestre de la Universidad Nacional de Chimborazo - Guairacaja Ramirez, Elvis Gustavo (2024)
The present research work on flipped classroom in learning definite integrals by fifth-semester students at the National University of Chimborazo stems from the need for students to have structured self-learning in topics covered in the syllabus of the integral calculus subject. In this research, learning guides and audiovisual materials (videos) were developed to teach definite integrals to fifth-semester students in the Pedagogy of Experimental Sciences Mathematics and Physics program at the National University of Chimborazo. It is a quantitative research with a non-experimental, propositional design. The topics of the integral calculus syllabus for the fifth semester were selected as the population. A bibliographic research was carried out, which allowed the incorporation of concepts such as flipped classrooms, didactic material, video scripts, and Kolb's cycle. It also details the essential topics in the subject syllabus related to the theme of definite integrals. Criteria were used to understand the reviewed concepts before their incorporation into the research work. Therefore, after applying the flipped classroom methodology to design didactic material, it can be concluded that it offers greater student participation in the learning process, thus personalizing their learning and developing critical thinking, leading to deeper and more meaningful learning. Therefore, this methodology improves the understanding and retention of mathematical concepts used to analyze the theme of definite integrals.